Diagnostic techniques for the detection of actinobacillus pleuropneumoniae the causative agent of porcine pleuropneumonia - Muñoz V., Dennis W. (Avances en Ciencias Veterinarias, 2005)
In this review the principal diagnostic techniques for the detection of Actinobacillus pleuropneumoniae (App) are described. A brief introduction about the most outstanding aspects of this important swine disease that causes great economics looses around the world is considered. The description of each technique will include their main advantages and disadvantages, and also the revolutionaries techniques that are under study. All this, in order to choose and standardize, a specific technique that should be sensible, fast and cheap for the national swine industry.